2016
DOI: 10.7821/naer.2016.1.132
|View full text |Cite
|
Sign up to set email alerts
|

Are All Children Equal? Causative Factors of Child Labour in Selected Districts of South Punjab, Pakistan

Abstract: The present study investigates the causative factors of child labour in selected districts of South Punjab, Pakistan. As member of the International Labour Organization (ILO) Pakistan has a responsibility to stamp out child labour from its regions. Our sample was selected from seven working environments (workshops, hotels, tea stalls, households, etc.) through purposive sampling. The data were collected via a questionnaire which was completed by a sample of 547 working children. The fi ndings of the explorator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Haider and Hussain (2014) narrated that descriptive research may be used to analyze any existing situation. It is a method of gathering data to test a hypothesis or react to research queries about the present and prior condition of the investigation (Haider & Qureshi, 2016). The two primary methods for gathering data are questionnaires and interviews.…”
Section: Methodsmentioning
confidence: 99%
“…Haider and Hussain (2014) narrated that descriptive research may be used to analyze any existing situation. It is a method of gathering data to test a hypothesis or react to research queries about the present and prior condition of the investigation (Haider & Qureshi, 2016). The two primary methods for gathering data are questionnaires and interviews.…”
Section: Methodsmentioning
confidence: 99%
“…The problem under investigation focuses on the present situation (prevailing or current condition) and keeping in view the nature of the study, the descriptive research design was found appropriate (Haider & Hussain, 2014;Haider & Qureshi, 2016). Among different designs, the survey was considered to be the most suitable to extract reliable results.…”
Section: Methodsmentioning
confidence: 99%
“…They are forced to do the job for them to sustain their needs. According to Haider and Qureshi (2016), since investing in children's education is typically viewed as the finest possible starting point for increased returns, children are perceived as human capital in every family structure. Because of a lack of information and due to culture, parents always thought that the best way possible was to invest in the child's education so that, in return, their child would help them financially as they got older and out of poverty.…”
Section: Research Problemmentioning
confidence: 99%